Thyroid Carcinoma Showing Thymic-Like Differentiation Causing Fracture of the Trachea - Aikaterini Marini; Meletios Kanakis; Konstantinos Valakis; Nikolaos Laschos; Maria Chorti; Achilleas Lioulias (Case Reports in Medicine)
Thyroid carcinoma showing thymic-like differentiation (CASTLE) comprises a rare neoplasm of the thyroid gland which arises from ectopic thymic tissue or remnants of brachial pouches. CASTLE is regarded as an indolent neoplasm with a favorable prognosis, irrespective of its metastatic potential. Diagnosis is difficult as clinicopathological features have not been yet well-defined. Radiological findings are not specific and only immunohistochemical positivity for CD5 and CD117 staining is highly suggestive of CASTLE. Despite lack of universally accepted treatment recommendations, the mainstay treatment includes thyroidectomy and systematic lymph node dissection. We report a case of CASTLE tumour with very uncommon characteristics developed in a 76-year-old man, who presented with rapidly deteriorating dyspnea and severe cough, resulting in respiratory failure. At surgery, a suspicious looking tumour arising from the upper pole of the right lobe of the thyroid gland, surrounding the trachea and displacing the right common carotid artery, was identified. The patient underwent en bloc resection of the tumour with the thyroid gland and regional lymph node dissection. This is the first reported case of CASTLE causing tracheal ring fracture.